Putuvaiyil Pārati : Putuvaiyil pattāṇṭukaḻ vālnta Pāratiyāriṉ vāḻkkaic carittiram - Campantam, Tiru., 1917- (Maṇivācakar Patippakam, 1982)
Life and writings of Pāratiyār, 1882-1921, Tamil litterateur and Indian freedom fighter, during his ten-year stay in Pondicherry.